Anaesthesia practices for endovascular therapy of acute ischaemic stroke: a Nordic survey. Issue 8 (2nd July 2017) - Rasmussen, M.; Simonsen, C. Z.; Sørensen, L. H.; Dyrskog, S.; Rusy, D. A.; Sharma, D.; Juul, N.
Abstract : Background: The optimal method of anaesthesia for endovascular therapy (EVT) in acute ischaemic stroke (AIS) has not been identified. Nordic departments of anaesthesiology may handle EVT cases for AIS differently. The aim of this survey was to describe the current practice patterns of Nordic anaesthesia departments in anaesthetic management of EVT in AIS. Methods: A survey consisting of 13 questions was sent to one qualified individual at all Nordic departments of anaesthesiology who manage anaesthesia for EVT interventions. The individual completed the questionnaire on behalf of their department. Results: Response rate was 100%. The majority of departments (84%) managed all EVT cases at their respective centres. Most departments have institutional guidelines on anaesthetic management (84%) including blood pressure management (63%) and were able to provide a 24‐h immediate response to an EVT request (63%). Conscious sedation was favoured by 68% of the departments using a variety of sedation protocols. Propofol and remifentanil was preferred for GA (58%). Emergent conversion to GA due to uncontrolled patient movements or loss of airway was experienced by 82% and 35% of the departments, respectively. Majority of the departments (89%) responded that non‐specialist anaesthetists occasionally handle EVT cases. Conclusions: This survey indicates that the majority of Nordic anaesthesia departments who manage anaesthesia for EVT are able to provide immediate 24‐h response to an EVT request. Most of these departments have institutional guidelines for EVT anaesthesia and haemodynamic management. Conscious sedation appears to be the preferred method of anaesthetic care.